Gender bias in candidate turnover: A longitudinal analysis of legislative elections in Flanders/Belgium (1987–2019). (November 2022) - Muyters, Gertjan; Put, Gert-Jan; Maddens, Bart
A higher candidate turnover among women may be one of the reasons why quota rules seldom succeed in attaining full legislative parity. This proposition is tested on the basis of a longitudinal analysis of 11, 678 candidates for legislative elections during the period 1987–2019 in the Flemish region of Belgium. It is shown that male candidates have shorter careers than women, contrary to expectations. The duration of the career as a candidate depends on the electoral performance, but only for men. In the long run, the introduction of a strict quota rule prolongs the candidate careers of both men and women, but the effect for women is much stronger. This finding contradicts the allegation that quota lead to an influx of unmotivated women candidates with a high turnover.